Association and Interactions between DNA Repair Gene Polymorphisms and Adult Glioma - Liu, Yanhong (2009)
It is generally accepted that glioma develops through accumulation of genetic alterations. We hypothesized that polymorphisms of candidate genes involved in the DNA repair pathways may contribute to susceptibility to glioma. To address this possibility, we conducted a study of 373 Caucasian glioma cases and 365 cancer-free Caucasian controls to assess associations between glioma risk and 18 functional SNPs in DNA repair genes. We evaluated potential gene-gene and gene-environment interactions using a multi-analytic strategy combining logistic regression, multifactor dimensionality reduction (MDR), and classification and regression tree (CART) approaches. In the single-locus analysis, six SNPs (ERCC1 3’ UTR, XRCC1 R399Q, APEX1 E148D, PARP1 A762V, MGMT F84L, and LIG1 5’UTR) showed a significant association with glioma risk. In the analysis of cumulative genetic risk of multiple SNPs, a significant gene-dosage effect was found for increased glioma risk with increasing numbers of adverse genotypes involving the above-mentioned six SNPs (P (trend) = 0.0004). Further, both the MDR and CART analyses identified MGMT F84L as the predominant risk factor for glioma, and revealed strong interactions among ionizing radiation (IR) exposure, PARP1 A762V, MGMT F84L and APEX1 E148D. Interestingly, the risk for glioma was dramatically increased in IR exposure individuals who had the wild-type genotypes of both MGMT F84L and PARP1 A762V [adjusted odds ratios (OR), 5.95; 95% confidence intervals (CI), 2.21–16.65]. Taken together, these results suggest that polymorphisms in DNA repair genes may act individually or together to contribute to glioma risk.